2023
DOI: 10.1097/acm.0000000000005136
|View full text |Cite
|
Sign up to set email alerts
|

Personal Financial Wellness Curricula for Medical Trainees: A Systematic Review

Abstract: PurposeEducation debt, poor financial literacy, and a late start to retirement savings can cause financial stress among physicians. This systematic review identifies methods for curriculum development, methods for curriculum delivery, and outcome measures to evaluate the effectiveness of personal financial wellness curricula for medical students, residents, and fellows. MethodThe authors searched the Embase, MEDLINE (via EBSCO), Scopus, Education Resources Information Center (via EBSCO), and Cochrane Library d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
(183 reference statements)
0
9
0
Order By: Relevance
“…In our sample of respondents, only 12% had a formal nancial literacy curriculum as a mandatory component of their residency Importantly, our study demonstrates that residents are strongly interested in the implementation of a formal curriculum and that residents wish to have a physician perspective, radiologist or not. Two systematic reviews on current personal nance training programs for medical trainees demonstrated that the majority of the primary studies rely on physician instructors (Igu et al, 2022;Wesslund et al, 2023). It is probable that residents wish to be taught by physicians who have an implicit understanding of their training journey through medical training and can offer guidance as they start their career.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our sample of respondents, only 12% had a formal nancial literacy curriculum as a mandatory component of their residency Importantly, our study demonstrates that residents are strongly interested in the implementation of a formal curriculum and that residents wish to have a physician perspective, radiologist or not. Two systematic reviews on current personal nance training programs for medical trainees demonstrated that the majority of the primary studies rely on physician instructors (Igu et al, 2022;Wesslund et al, 2023). It is probable that residents wish to be taught by physicians who have an implicit understanding of their training journey through medical training and can offer guidance as they start their career.…”
Section: Discussionmentioning
confidence: 99%
“…The desired topics of nancial education do shift throughout a physician's career but are still greatly desired, no matter the time (MD, 2019). From prior studies, some topics of interests to residents include managing student loans, disability insurance, retirement savings, and general personal nance (Wesslund et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate the work Wesslund and colleagues 1 conducted in their review of personal financial wellness curricula and agree with their conclusions. Implementation of personal finance courses during medical training provides a unique avenue for combatting personal stress and physician burnout.…”
mentioning
confidence: 99%
“…Given that debt is a nearly unavoidable reality, strengthening the financial literacy skills of physicians-in-training is an important and worthy goal, as discussed by Wesslund et al 26 in their systematic review in this issue of Academic Medicine. The authors identified 13 published studies of 13 personal financial wellness curricula for medical students, residents, and/ or fellows.…”
mentioning
confidence: 99%